Effectiveness of plant-derived proanthocyanidins on demineralization on enamel and dentin under artificial cariogenic challenge - da Silva, Ana Paula Pereira [UNESP]; Gonçalves, Rafael Simões; Borges, Ana Flávia Sanches; Bedranrusso, Ana Karina; Shinohara, Mirela Sanae [UNESP] (FapUNIFESP (SciELO), 2015)
Dental caries is considered a disease of high prevalence and a constant problem in public health. Proanthocyanidins (PAs) are substances that have been the target of recent studies aiming to control or treat caries. Objective: The aim of this in vitro study was to evaluate the efficacy of a treatment with grape seed extract, under cariogenic challenge, to minimize or even prevent the onset of caries in the enamel and dentin. Material and Methods: Blocks of enamel and dentin (6.0x6.0 mm) were obtained from bovine central incisors, polished, and selected by analysis of surface microhardness (SH). The blocks were randomly divided into 3 groups (n=15), according to the following treatments: GC (control), GSE (grape seed extract), GF (fluoride – 1,000 ppm). The blocks were subjected to 6 daily pH cycles for 8 days. Within the daily cycling, the specimens were stored in buffered solution. The blocks were then analyzed for perpendicular and surface hardness and polarized light microscopy. Results: The means were subjected to statistical analysis using the ANOVA and Fisher’s PLSD tests (p<0.05). For enamel SH, GF showed the highest hardness values. In the dentin, GF was also the one that showed higher hardness values, followed by GSE. Regarding the cross-sectional hardness values, all groups behaved similarly in both the enamel and dentin. The samples that were treated with GSE and fluoride (GF) showed statistically higher values than the control. Conclusion: Based on the data obtained in this in vitro study, it is suggested that grape seed extract inhibits demineralization of artificial carious lesions in both the enamel and dentin, but in a different scale in each structure and in a smaller scale when compared to fluoride.
Keywords: Dental caries; Dental enamel; Dentin; Hardness; Proanthocyanidins